Improving critical thinking skills of high school students through guided inquiry implementation for learning reaction rate concept in chemistry - Mila Meita Sari; Muchlis Muchlis (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2022)
This research was conducted to know (1) the implementation of the guided inquiry learning model; (2) student activities; (3) critical thinking skills; and (4) student responses. The type of research was used pre-experimental with one group pretest-posttest design. The population in this research was all students of class XI MIPA SMAN 1 Gedangan Sidoarjo in the 2021/2022 academic year, with 11th grade MIPA 6 as the sample. The research results show that the learning model is implemented in the very good category with the percentage of implementation at first is 96.09% and the second meetings are 98.83%. The activity of students is very good and supports the effectiveness of the learning model, with the percentage at the first and second meetings being 97.9% and 98.7%, respectively. (3) There was an increase in critical thinking skills from acquiring the N-Gain score, 87.10% of students in the high category and 12.90% of students in the medium category, and the classical student learning outcomes are 87.10%. (4) Student response to the learning model that has been applied is very good, with a percentage of 90.37%. Based on this, it indicated that the guided inquiry model could improve the critical thinking skills of 11th grade students on the reaction rate material.